Transcriptome Analysis in the Head Kidney of Rainbow Trout (Oncorhynchus mykiss) Immunized with a Combined Vaccine of Formalin-Inactivated Aeromonas salmonicida and Vibrio anguillarum - Jongwon Lim (MDPI AG, 2021)
This study aimed to identify the molecular mechanisms regulated by a combined vaccine against Aeromonas salmonicida and Vibrio anguillarum (O1 serotype). These bacteria cause furunculosis and vibriosis, respectively, and are associated with a high mortality in rainbow trout in Korea. The vaccine upregulated gene expression of TCRα, T-bet, sIgM, and mIgM, markers of an activated adaptive immune response. On days 1, 3, and 5, transcriptome analysis revealed 862 (430 up- and 432 downregulated), 492 (204 up- and 288 downregulated), and 741 (270 up- and 471 downregulated) differentially expressed genes (DEGs), respectively. Gene ontology (GO) enrichment analysis identified 377 (108 MF, 132 CC, 137 BP), 302 (60 MF, 180 CC, 62 BP), and 314 (115 MF, 129 CC, 70 BP) GOs at days 1, 3, and 5, respectively. Kyoto Encyclopedia of Genetic and Genomic enrichment analysis identified eight immune system-related pathways like cytokine-cytokine receptor interaction, NF-kappaB signaling pathway, TNF signaling pathway, NOD-like receptor signaling pathway, cytosolic DNA sensing pathway, cell adhesion molecule, complement and coagulation cascade, and antigen processing and presentation. In the analysis of the protein–protein interaction of immune-related DEGs, a total of 59, 21, and 21 interactional relationships were identified at days 1, 3, and 5, respectively, with TNF having the highest centrality at all three time points.